Matrix association region/scaffold attachment region : the crucial player in defining the positions of chromosome breaks mediated by bile acid-induced apoptosis in nasopharyngeal epithelial cells - Tan, Sang-Nee; Sim, Sai-Peng (BMC Medical Genomics, 2019)
It has been found that chronic rhinosinusitis (CRS) increases the risk of developing nasopharyngeal carcinoma (NPC). CRS can be caused by gastro-oesophageal reflux (GOR) that may reach nasopharynx. The major component of refluxate, bile acid (BA) has been found to be carcinogenic and genotoxic. BA-induced apoptosis has been associated with various cancers. We have previously demonstrated that BA induced apoptosis and gene cleavages in nasopharyngeal epithelial cells. Chromosomal cleavage occurs at the early stage of both apoptosis and chromosome rearrangement. It was suggested that chromosome breaks tend to cluster in the region containing matrix association region/scaffold attachment region (MAR/SAR). This study hypothesised that BA may cause chromosome breaks at MAR/SAR leading to chromosome aberrations in NPC. This study targeted the AF9 gene located at 9p22 because 9p22 is a deletion hotspot in NPC.